PENGARUH KOMPENSASI, LINGKUNGAN KERJA DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN PABRIK GULA ASSEMBAGOES DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Adzania, Rifanda Tirta; Pramesthi, Riska Ayu; Soeliha, Siti (Fakultas Ekonomi dan Bisnis, 2024)
Companies cannot be separated from having quality human resources; this will have an impact on the sustainability of the company's goals, superior, professional and competitivehuman resources which will have a positive impact on the company's success. The aim of this research is to analyze and test the influence of Compensation, Work Environment and Work Culture on the Performance of Assembagoes Sugar Factory Employees with Job Satisfaction as an Intervening Variable. This research is explanatory research. The populations in this study were contract employees of the Assembagoes Sugar Factory. The sampling technique is determined by quota sampling. The data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS3.0 application, show that Compensation has a positive but not significant effect on Job Satisfaction, Work Environment has a positive and significant effect on Job Satisfaction, Work Culture has a positive and significant effect on Job Satisfaction, Compensation has a positive but not significant effect on Performance, work environment has a positive but not significant effect on performance, work culture has a positive and significant effect on performance.